Difficult patients from the perspective of healthcare workers: a study at a public hospital - Akyüz, Selahattin; Biyik, Erhan; Yalçin-Balçik, Pınar (International Journal of Research in Medical Sciences, 2017)
Background: The purpose of the study is to identify the frequency of encounters with difficult patients, the level of patient difficulty and the demographic characteristics of difficult patients from the perception of healthcare workers. Methods: The data have been obtained from the health workers who are employed at a public hospital in the city of Ankara and are in interaction with patients. The data have been obtained with the “difficult patient and healthcare personnel interaction survey”. Results: It has been determined that approximately 2 out of every 10 patients (=2.11) which the healthcare workers encounter during the day are difficult patients and the level of difficulty of these patients is low (=3.62). It has been found that there is a medium level, positive and significant relationship between patient difficulty and seductive behavior and that seductive behavior has a significant effect on patient difficulty. It has been found that there is a medium level, positive and significant relationship between the discomfort experienced by the personnel and seductive behavior and that seductive behavior has a significant effect on the discomfort experienced by the personnel. Conclusions: As a result, it can be seen that nearly a fifth of all patients are perceived as difficult by healthcare workers. It is believed that healthcare workers should be informed about the characteristics of difficult patients and the aspects which should be taken into consideration while interacting with these patients and thereby more effective form of communication will be established at medical institutions.